2009
DOI: 10.1002/lary.20647
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery for oropharyngeal squamous cell carcinoma: A prospective study of feasibility and functional outcomes

Abstract: Transoral robotic surgery is a safe and efficacious method of surgical treatment of oropharyngeal neoplasms. Advantages of the technique include adequate ability to visualize and manipulate with two hands lesions in the base of tongue. Patients were able to retain or rapidly regain oropharyngeal function in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
373
4
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 332 publications
(409 citation statements)
references
References 17 publications
23
373
4
9
Order By: Relevance
“…The oncologic contraindications are fixation of the tumor, direct extension to the cervical lymph nodes, extension of tumor to the lateral pharyngeal wall, distant metastasis/ unresectable nodal disease/skin metastasis, or involvement of [50 % of the BOT or to such an extent that major flap reconstruction would be necessary to close defect (relative contraindication). The anatomic contraindications include severe trismus, pharyngeal/tongue crowding preventing adequate tumor exposure, and the presence of a retropharyngeal carotid artery [30,31]. Physiologic contraindications are related to patient comorbidities that would prevent general anesthesia or decrease the ability to heal by secondary intention.…”
Section: Managementmentioning
confidence: 99%
“…The oncologic contraindications are fixation of the tumor, direct extension to the cervical lymph nodes, extension of tumor to the lateral pharyngeal wall, distant metastasis/ unresectable nodal disease/skin metastasis, or involvement of [50 % of the BOT or to such an extent that major flap reconstruction would be necessary to close defect (relative contraindication). The anatomic contraindications include severe trismus, pharyngeal/tongue crowding preventing adequate tumor exposure, and the presence of a retropharyngeal carotid artery [30,31]. Physiologic contraindications are related to patient comorbidities that would prevent general anesthesia or decrease the ability to heal by secondary intention.…”
Section: Managementmentioning
confidence: 99%
“…Moore et al [23] at The Mayo Clinic reported a prospective series of 45 patients with T1-T4 squamous cell carcinoma of the base of tongue or tonsillar fossae who were all treated with TORS. They found that TORS was safe and feasible and reported that all of the 45 TORS procedures performed were resected with negative margins.…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 99%
“…Moore et al performed TORS on 45 patients, and 82 % of patients were tolerating an oral diet by the first post-operative visit. Seventeen percent of patients required a feeding tube, but none required assistance with feeding at 1-year follow-up [23]. Hurtuk et al [32] also described an early return to oral diet with all 54 patients in their study tolerating oral diet on the day of surgery.…”
Section: Functional Outcomes and Quality Of Lifementioning
confidence: 99%
“…The present study compares the adverse effects of surgical removal of histologically-proven T1 and T2 scc of tongue base and supraglottis, performed by two different techniques, namely by conventional open surgery (os) and Tors (ref. [10][11][12] ). To the best of our knowledge -such a comparison has not been made so far.…”
Section: Introductionmentioning
confidence: 99%